Participation of Women Farmers Group Members on Pekarangan Pangan Lestari (P2L) Program In Kendari City Southeast Sulawesi - Arianti, Fitri; Taridala, Sitti Aida Adha; Sadimantara, Fahria Nadiryati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2021)
This study aims to determine the participation rate of Women Farmers Group members in implementing the Pekarangan Pangan Lestari program in Kendari City and analyze the relationship between the participation rate with internal and external factors of Women Farmers Group members in the Pekarangan Pangan Lestari program. The research was conducted in June-July 2021. The population in this study was 53 members of the Women Farmers Group. Using the census method, 53 group members were obtained as research samples. The variables of this research are the participation rate, internal factors, and external factors. Data analysis used descriptive statistical analysis through the Likert scale measuring tools and Spearman Rank correlation. The results showed that the participation rate of Women Farmers Group members in implementing the Pekarangan Pangan Lestari program was the Seruni Women Farmers Group was in the medium category, and the Mekopoaso Women Farmers Group was in the high sort. The relation between the participation rate with internal and external factors of the Women Farmers Group members in the Pekarangan Pangan Lestari is the participation rate obtained which is significantly related to internal factors, namely the level of education and type of work, and external factors, namely the availability of agricultural tools and facilities.